Decomposing changes in income risk using consumption data - Richard Blundell; Hamish Low; Ian Preston (Institute for the Study of Labor (IZA), 2011)
We develop a new approach to the decomposition of income risk within a nonstationary model of intertemporal choice. The approach allows for changes in income risk over the life-cycle and with the business cycle. It requires only repeated cross-section data and can allow for mixtures of persistent and transitory components in the dynamic process for income. Evidence from a stochastic simulation of consumption choices in a nonstationarity environment is used to show the robustness of the method for decomposing income risk. The approach is used to investigate the changes in income risk in Britain across the inequality growth period from the late 1970s to the late 1990s. Peaks in the variance of permanent shocks are shown to occur in the middle of the 1980s and the early 1990s.
urn:nbn:de:101:1-201112121768
Keywords: C30; D52; D91; 330; income risk; consumption; nonstationarity; inequality; Einkommensverteilung; Soziale Ungleichheit; Konsumentenverhalten; Risiko; Großbritannien